About Regularization of Severely Ill-Posed Problems by Standard Tikhonov's Method with the Balancing Principle - Solodky, Sergei G.; Myleiko, Ganna L. (Mathematical Modelling and Analysis, 2014)
In the present paper for a stable solution of severely ill-posed problems with perturbed input data, the standard Tikhonov method is applied, and the regularization parameter is chosen according to balancing principle. We establish that the approach provides the order of accuracy on the class of problems under consideration.